Myxoid Leiomyosarcoma of the Uterus in a Fertile Woman - Vito Leanza; Alfi o D'Agati; Gianluca Leanza; Carlo Pafumi; Mayada Chammas; Antonio Carbonaro (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2017)
A 37 year old woman (G1P1 spontaneous delivery) was admitted to our university hospital for menometrorrhagia. The case history showed the patient had menometrorrhagia for six months; moreover, during the abdominal examination we found a mass occupying the hypogastric and mesogastric area. The consistence was hard and the mass reached the level of the umbilicus. The combined vaginal-abdominal examination confirmed the presence of the mass on the anterior wall and, in addition, multiple myomata were felt; the uterus was found enlarged in size (equivalent to 18 pregnancy weeks); both ovaries and Fallopian tubes were regular. During surgery multiple myomata were visualized. The largest, 10 centimeter diameter, was soft in consistence with a gelatinous structure. Total abdominal hysterectomy with preservation of adnexa was performed. Histopathological result gave evidence of myxoid leiomyosarcoma for the largest myoma, whereas the other nodes were benign.